Study and implementation of a low complexity receiver using TCH codes - Oliveira, João André Calado de (2021)
The use of coding in telecommunications systems reveals to be a technique with an essential contribution to the improvement of the recovery of transmitted signals. Depending on the circumstances to which a signal is subjected at transmission, by recurring to coding, it is possible to attenuate the unfavorable effects that result from this process, obtaining a signal with superior quality in comparison with a scenario where the presence of coding is absent. This study aims to test the feasibility of a high-rate wireless communications system using TCH codes being applied to an OFDM signal, subjected to noise components introduced by a wireless AWGN channel, considering a free path propagation model. Due to their correlation properties, the use of TCH codes reveals to be adequate since they allow the same codewords to be used to realize both error correction and channel estimation, mitigating the channels effects, leading to the realization of a receiver with lower complexity. With the intent of performing a qualitative analysis to this system, a simple simulation is executed in MATLAB where an OFDM signal is generated, being therefore applied various TCH codes and, through channel estimation, obtain the BER for their respective code lengths and, consequently, coding gains. The results were obtained for the modulation indexes of 16, 64 and 256-QAM. These demonstrate that the implementation of TCH codes is a viable option to reduce the rate of recovered errors, enabling the reception of a signal with better reliability, especially for higher code lengths and modulation indexes.